Karakterisasi sekuen DNA gen mtCO-1 hama penggerek pucuk (Hypsipyla sp.) pada tanaman mahoni (Swietenia macrophylla King) di Kabupaten Minahasa dan Kota Tomohon Provinsi Sulawesi Utara - Jusuf Manueke; Jefry Sembiring; Dantje Tarore (Jurnal Entomologi Indonesia, 2020)
Hypsiphyla sp. include the Order Lepidoptera, Family Pyralidae. These insects is one of the important pests on mahogany plants (Swietenia macrophylla King.).  This pest has been found to attack S. macrophylla plants in North Sulawesi, especially in the area of mahogany plant centers namely North Minahasa Regency and Tomohon City. The aim of the study was to determine the CO1 gen profile of mahogany shoots borer (Hypsipyla sp.) on mahogany plant (Swietenia macrophylla) in Minahasa Regency and Tomohon City, North Sulawersi Province. The method used is descriptive method, consists of extraction or purification of total double strands DNA (dsDNA), amplification of CO1 gene by PCR method, visualization of PCR results with atomatic electrophoresis qiagen, and sequencing. The sequenced data that is the construction of the phylogeny tree are described according to clusters which give the morphometric character of each sample. The results of the analysis of genetic differences between Hypsipyla sp. origin of North Minahasa and Tomohon namely 3.8%–4.4%. Hypsipyla sp. origin of North Minahasa and Tomohon with H. grandella namely 9.0%–9.3%. Based on the results of this analysis it can be seen that the kinship of Hypsipyla sp. in North Minahasa Regency and Tomohon City it is closer to H. robusta than H. grandella. Results of cluster analysis of Hypsipyla sp. in North Minahasa Regency and Tomohon City, North Sulawesi Province compared to H. robusta and H. grandella in the Gen Bank mapped in the phylogeny tree construction indicate that Hypsipyla sp. in North Mihasa Regency and Tomohon City, North Sulawesi Province already exists or forms a separate clade with H. robusta and H. grandella clades in Bank Gen.